Special physical training system design for initial specialization stage in football - Zlygostev, O. V.; Tatyanenko, S. A.; Guba, V. P. (Theory and Practice of Physical Culture, 2019)
Initiatives to improve training process efficiency and effectiveness in modern youth football give a growing priority to the relevant training methods and tools to step up the special physical fitness; with a special role played by the speed-strength building ones - critical for the competitive progress [1, 4]. The study offers and tests benefits of a special speed-strength prioritizing physical training system design for the beginner specialization stage in youth football. The model was designed on a purposeful modular basis with an emphasis on the speed-strength training component. Sampled for the model testing experiment were the 12-14 year old football players from the Children and Youth Sport School in Tobolsk, Tyumen Oblast, split up into three Experimental Groups (EG) and one Reference Group (RG), with the latter trained as required by the standard training system. The key role for the speed-strength training in the new model was played by the special training modules dominated by the speed, strength and speed strength building practices, with every module offering unspecific and specific ball handling sets of practices. The new categorical speed-strength training modules were included in an annual training process cycle on a customizable basis. The model testing experiment proved its benefits as verified by the EG significant progress versus the RG in the speed-strength qualities and competitive performance over the annual training cycle.